Mechanical properties of recycled concrete with demolished waste concrete aggregate and clay brick aggregate - Zheng, Chaocan; Lou, Cong; Du, Geng; Li, Xiaozhen; Liu, Zhiwu; Li, Liqin (Results in physics, 2018)
•Compressive strength of concrete containing recycled concrete aggregate or recycled brick aggregate is investigated experimentally.•Effect of replacement rate of coarse aggregate on the strength of hardened concrete is examined.•Two kinds of concrete are compared in terms of the compressive strength.•Effect of particle optimal gradation on the compressive strength is investigated. This paper presents an experimental investigation on the effect of the replacement of natural coarse aggregate (NCA) with either recycled concrete aggregate (RCA) or recycled clay brick aggregate (RBA) on the compressive strengths of the hardened concrete. Two grades (C25 and C50) of concrete were investigated, which were achieved by using different water-to-cement ratios. In each grade concrete five different replacement rates, 0%, 25%, 50%, 75% and 100% were considered. In order to improve the performance of the recycled aggregates in the concrete mixes, the RCA and RBA were carefully sieved by using the optimal degradation. In this way the largest reduction in the 28-day compressive strength was found to be only 7.2% and 9.6% for C25 and C50 recycled concrete when the NCA was replaced 100% by RCA, and 11% and 13% for C25 and C50 recycled concrete when the NCA was replaced 100% by RBA. In general, the concrete with RCA has better performance than the concrete with RBA. The comparison of the present experimental results with those reported in literature for hardened concrete with either RCA or RBA demonstrates the effectiveness in improving the compressive strength by using the optimal gradation of recycled aggregates.